2011
DOI: 10.1007/s00586-011-1691-z
|View full text |Cite
|
Sign up to set email alerts
|

CRPS I following artificial disc surgery: case report and review of the literature

Abstract: We report a case of type 1 complex regional pain syndrome (CRPS I) of the left leg following the implantation of an artificial disc type in the L4/5 segment of the lumbar spine using a midline left-sided retroperitoneal approach. This approach included the mobilisation of the sympathetic trunk with incision and resection of the intervertebral disc. The perioperative and immediate postoperative periods were uneventful, but on the second postoperative day the patient complained of a progressive allodynia of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Complex regional pain syndrome has been reported after various posterior lumbar procedures, including decompression/ fusion, hemilaminectomy, microdiscectomy, and artificial disc implantation. 17,25 To the authors' knowledge, this is the first report of CRPS following a lateral lumbar approach. …”
mentioning
confidence: 80%
See 2 more Smart Citations
“…Complex regional pain syndrome has been reported after various posterior lumbar procedures, including decompression/ fusion, hemilaminectomy, microdiscectomy, and artificial disc implantation. 17,25 To the authors' knowledge, this is the first report of CRPS following a lateral lumbar approach. …”
mentioning
confidence: 80%
“…Some have questioned the diagnostic rigor by which patients were assumed to have CRPS in this study. 14 Knoeller et al 17 reported a case of CRPS following an anterior midline retroperitoneal approach for implantation of a lumbar artificial disc at the L4-5 level. The patient postoperatively experienced pain and temperature changes associated with subjective weakness not confirmed by confrontational testing.…”
Section: Current Case Of Postoperative Rsd and Comparison With Prior mentioning
confidence: 99%
See 1 more Smart Citation
“…Anyhow, CRPS I can also occur following spine surgery. One of the possible mechanisms might be a sympathetic reaction following the mobilization of the sympathetic trunk during ventral access to the spine, as the case of CRPS following lumbar disc prosthesis shows (tables 1, 2) [18]. …”
Section: Discussionmentioning
confidence: 99%
“…The nonspinal complications of LTDR are classed as intraoperative (injury to ureter, nerves, 378 or large vessels 71,433 ) or postoperative (infection, 404 retrograde ejaculation, wound problems, hematoma, 71 formation of retroperitoneal lymphocele 401 ) and are common to all LTDR procedures that adopt an anterior lumbar surgical approach, irrespective of the LAD used. Although a less-invasive lateral approach 313,420 or a laparoscopic approach 430 for LTDR may impact the risk of the aforementioned and other complications, these innovations do not fulfill our a priori criteria for meaningful comment.…”
Section: Nonspinal Complications Of Ltdrmentioning
confidence: 99%